2015
DOI: 10.1177/1024529414563004
|View full text |Cite
|
Sign up to set email alerts
|

Explaining declining industries in developing countries: The case of textiles and apparel in Ghana

Abstract: Although declining industries have garnered a plethora of scholarly attention, there is still a theoretical deficit in our understanding of factors that precipitate them in developing countries. This paper examines the causes of declining industries in developing countries. The paper develops an integrated framework to shed light on the subject. Using insights from the textile and apparel industries in Ghana, the study uncovered factors such as global competition, the growth of second-hand clothing and smuggli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…However the literature and economic logic suggest that this "recycling route" adversely affects the local textile manufacturing industry in Africa (Amankwah-Amoah, 2015, Hawley, 2006aand Hawley, 2006bBaden and Barber, 2005) and again is encouraging in developing alternative approaches. Traditional mechanical recycling converts the waste garments by pulling the fabric into yarns and fibres and then reconstituting back into either recycled yarns for textile applications or into other applications such as nonwoven products, carpet underlay, sound insulators, thermal insulators, phase change materials, geo-textile materials, odour removal material, filtration material, and many others (DEFRA, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However the literature and economic logic suggest that this "recycling route" adversely affects the local textile manufacturing industry in Africa (Amankwah-Amoah, 2015, Hawley, 2006aand Hawley, 2006bBaden and Barber, 2005) and again is encouraging in developing alternative approaches. Traditional mechanical recycling converts the waste garments by pulling the fabric into yarns and fibres and then reconstituting back into either recycled yarns for textile applications or into other applications such as nonwoven products, carpet underlay, sound insulators, thermal insulators, phase change materials, geo-textile materials, odour removal material, filtration material, and many others (DEFRA, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that at least 50% of the waste apparel collected by developed countries is transported to developing countries to be used as second hand clothing (Ekström & Salomonson, 2014). In addition this second hand clothing business hinders the growth of textile and fashion industries in the developing countries, while the solid waste management cost in the developed source countries is also increasing (Amankwah-Amoah, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This surpassed that of the country's traditional sources of imports. However, the influx of relatively cheap textiles and garment from China is crowding out local garment producers in developing countries like Uganda (Amankwah-Amoah, 2015). Garment producers in Uganda have found it extremely difficult to compete with the low cost alternatives from China considering the fact that they are appealing to many low-income earners.…”
Section: How Does China Fit Into the Garment Sector In Uganda?mentioning
confidence: 99%